The Impact of Initial Composition on Massive Star Evolution and Nucleosynthesis - Christopher West; Alexander Heger; Benoit Côté; Lev Serxner; Haoxuan Sun (The Astrophysical Journal, 2025)
We study the sensitivity of presupernova evolution and supernova nucleosynthesis yields of massive stars to variations of the initial composition. We use the solar abundances from Lodders, and compute two different sets of initial stellar compositions: (i) scaled solar abundances and (ii) the isotopic galactic chemical history model (GCH) developed by C. West & A. Heger. We run a grid of models using the KEPLER stellar evolution code, with 7 initial stellar masses, 12 initial metallicities, and the 2 scaling methods, to explore the effects on nucleosynthesis over a metallicity range of −4.0 ≤ [ Z ] ≤ +0.3. We find that the compositions from the GCH model better reproduce the weak s -process peak than the scaled solar models. The model yields are then used in the OMEGA Galactic Chemical Evolution (GCE) code to assess this result further. We find that initial abundances used in computing stellar structure have a larger impact on the GCE results than the initial abundances used in the large nuclear co-processing network, with the GCH model again being favored when compared to observations. Finally, a machine learning algorithm was used to verify the free parameter values of the GCH model, which were previously found by C. West & A. Heger using a stochastic fitting process. The updated model is provided as an accessible tool for further nucleosynthesis studies.